Advances in genetic profile and therapeutic strategy of pulmonary large cell neuroendocrine carcinoma - Zhu, Siyu; Wang, Xinyue; Li, Hui; Zhao, Peiyan; Liu, Jingjing; Zhang, Liang; Cheng, Ying (Frontiers in Medicine, 2024)
Pulmonary large cell neuroendocrine carcinoma (LCNEC) is a high-grade neuroendocrine carcinoma (HGNEC) accounting for 3% of primary lung cancer, and characterized by strong invasion, high heterogeneity, and extremely poor prognosis. At present, the diagnosis and treatment of LCNEC remains controversial and refer to therapeutic strategy of small cell lung cancer (SCLC), lacking precise therapy. Recently, the genetic analysis and clinical trials of LCNEC gradually emerged, providing more evidence for precise diagnosis and treatment. Here, we review the diagnosis, molecular characteristics, and treatment of LCNEC based on the existing research and frontier progress to provide a potential direction for future diagnosis and treatment of LCNEC.